Projeto de impermeabilização de acordo com a NBR ABNT 9575/2010 aplicado a uma residência unifamiliar: uma análise de custos - Lorenzet, Renata (2023)
The presence of water in the built structure not only reduces the longevity of materials, but also accelerates the degradation of the structure itself. Effective humidity control emerges as one of the main pillars to mitigate pathological manifestations, thus providing greater durability to the building. The absence of adequate waterproofing not only results in significant additional costs for corrections, but also causes discomfort and challenges as soon as pathological manifestations begin to manifest. It is expected that the buildings, upon completion, will ensure a minimum level of comfort and functionality for residents. The development of an executive waterproofing project has a minimal financial impact on the building's budget in the face of pathological manifestations that result from the lack of application of waterproofing products. This work aimed to develop an executive waterproofing project for a singlefamily residence, considering the specific type of humidity in each area. The project also specified the most suitable materials and correct execution techniques, in addition to estimating the percentage of cost associated with waterproofing. The cost of waterproofing was estimated based on the SINAPI Table, resulting in a percentage of 4.57% in relation to the total cost of the building. It is crucial to highlight that the effective functioning of the waterproofing system can only be validated through strict adherence to what was proposed in the project, the choice of specialized labor and the use of materials duly certified in accordance with regulatory standards. Proper maintenance is also essential if the system requires future interventions.